HOLMES AND POIROT’S CHARACTERIZATION IN DOYLE’S VALLEY OF FEAR AND CHRISTIE’S THE MURDER OF ROGER ACKROYD (A Comparative Study with Biographical Approach) - DEWI, CANDRA PUSPITA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Characterization is the process of creating a character, including: words, actions, thoughts,appearance, other peoples’ thoughts and perceptions about the character. In this study, the writercompares detectives’ characterization and investigates it with the biography of the authors of thenovels entitled Valley of Fear and The Murder of Roger Ackroyd. This study is conducted todiscover the differences between both Sherlock Holmes and Hercule Poirot’s characterization. This study reveals that Sherlock Holmes and Hercule Poirot’s characterization leads to somedifferences: (1) Holmes becomes enthusiastic and not giving up in facing the secret passwordalthough he knows that he was in danger if solving the case, while Poirot tends to relax andactually requested in advance by one of the relatives of victims to investigate the murder; (2)Holmes prefers to use his skill of deduction, observation, discussion, and makes a hypothesis toreveal the truth of the case; while Poirot tends to focus on order or organize the fact, analyze thecase with physiological aspects, and rearrange his ideas when face the dead end of the case. Asthe result, the way of the detectives face the case and the method they use are the differencesbetween Sherlock Holmes and Hercule Poirot’s characterization. The characterizations of both ofthem are influenced by the biography of the author. The writer suggests that more comprehensive studies on other main characters can be foundin detective’s novel or others. Recalling the importance of characterization that is influenced bythe author’s biography, the writer also suggests that future researchers investigate other intrinsicaspects of the novel such as theme, plot and setting and their relation to the author’s biography. Keywords: Characterization, Comparative Literature, Biographical Approach.